Automated facial expression analysis of participants self-criticising via the two-chair technique: exploring facial behavioral markers of self-criticism - Halamová, Júlia; Kanovský, Martin; Brockington, Guilherme; Strnádelová, Bronislava (Frontiers in Psychology, 2023)
Introduction: As self-rating scales are prone to many measurement distortions, there is a growing call for more objective measures based on physiological or behavioural indicators. Self-criticism is one of the major transdiagnostic factor of all mental disorders therefore it is important to be able to distinguish what are the characteristic facial features of self-criticizing. To the best of our knowledge, there has been no automated facial emotion expression analysis of participants self-criticising via the two-chair technique. The aim of this study was to detect which action units of facial expressions were significantly more often present in participants performing self-criticism using the two-chair technique. Methods: The non-clinical sample consisted of 80 participants (20 men and 60 women) aged 19 years to 57 years (M = 23.86; SD = 5.98). In the analysis we used iMotions’s Affectiva AFFDEX module (Version 8.1) to classify the participants’ actions units from the self-criticising videos. For the statistical analysis we used a multilevel model to account for the repeated-measures design. Results: Based on the significant results the self-critical facial expression may therefore comprise the following action units: Dimpler, Lip Press, Eye Closure, Jaw Drop, and Outer Brow Raise, which are related to contempt, fear, and embarrassment or shame; and Eye Closure and Eye Widen (in rapid sequence Blink), which are a sign that highly negative stimuli are being emotionally processed. Discussion: The research study need to be further analysed using clinical samples to compare the results.